2013
DOI: 10.1002/jgrd.50686
|View full text |Cite
|
Sign up to set email alerts
|

Application of spectral analysis techniques in the intercomparison of aerosol data: 1. An EOF approach to analyze the spatial‐temporal variability of aerosol optical depth using multiple remote sensing data sets

Abstract: Many remote sensing techniques and passive sensors have been developed to measure global aerosol properties. While instantaneous comparisons between pixel‐level data often reveal quantitative differences, here we use Empirical Orthogonal Function (EOF) analysis, also known as Principal Component Analysis, to demonstrate that satellite‐derived aerosol optical depth (AOD) data sets exhibit essentially the same spatial and temporal variability and are thus suitable for large‐scale studies. Analysis results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…These three modes, as shown in Fig. 9, are also consistent with Li et al (2013Li et al ( , 2014a and reveal aerosol-source regions and their interannual variability. It is encouraging that all four satellite data sets agree well with AERONET qualitatively.…”
Section: Global Analysis -Anomaly Data Setsupporting
confidence: 75%
See 1 more Smart Citation
“…These three modes, as shown in Fig. 9, are also consistent with Li et al (2013Li et al ( , 2014a and reveal aerosol-source regions and their interannual variability. It is encouraging that all four satellite data sets agree well with AERONET qualitatively.…”
Section: Global Analysis -Anomaly Data Setsupporting
confidence: 75%
“…Previously, we have demonstrated that spectral decomposition techniques such as principal component analysis (PCA) can be effectively used to examine the spatial and temporal variability in multidimensional aerosol observations (Li et al, , 2011(Li et al, , 2013. Many global and regional aerosol-source regions and their seasonal and interannual variability are successfully captured by the dominant orthogonal modes.…”
Section: Introductionmentioning
confidence: 99%
“…Black carbon, primary and secondary organics, and sulfate are maximal in this region during the summer, whereas mineral dust and sea salt peak in spring. A formal approach could include combined principal component analysis of the daily model-simulated or satelliteretrieved burdens of multiple aerosol components in candidate deployment regions (e.g., Li et al 2013).…”
Section: Deployment Site Selection and Completion Strategiesmentioning
confidence: 99%
“…The AOD products from these spaceborne sensors are mainly available in two levels, i.e., swath (Level-2) and gridded (Level-3) formats. Several studies involving aerosol characterization, aerosolclimate effects and aerosol trend analysis utilize the monthlymean gridded AOD products from MISR and MODIS (Level-3 data) (Shrestha and Barros, 2010;Zhang and Reid, 2010;Li et al, 2013). The Level-3 MODIS AOD dataset includes aerosol retrievals over ocean as well as DarkTarget retrievals over land (Levy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If the time series consists of a number of missing values above a certain threshold, the resultant trend obtained from the time series may not be a reliable or accurate representation of the change over time. Empirical Orthogonal Functions (EOFs) are another technique used widely in the seasonal decomposition of aerosols (or other environmental/climatic variables) based on satellite datasets (Shrestha and Barros, 2010;Li et al, 2013), where central to the EOF analysis is the variance-covariance matrix. The elements of this matrix are computed using the covariance between two time series.…”
Section: Introductionmentioning
confidence: 99%